2014
DOI: 10.1098/rspb.2014.1261
|View full text |Cite
|
Sign up to set email alerts
|

Social affiliation matters: both same-sex and opposite-sex relationships predict survival in wild female baboons

Abstract: Social integration and support can have profound effects on human survival. The extent of this phenomenon in non-human animals is largely unknown, but such knowledge is important to understanding the evolution of both lifespan and sociality. Here, we report evidence that levels of affiliative social behaviour (i.e. 'social connectedness') with both same-sex and opposite-sex conspecifics predict adult survival in wild female baboons. In the Amboseli ecosystem in Kenya, adult female baboons that were socially co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
263
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(321 citation statements)
references
References 76 publications
34
263
2
2
Order By: Relevance
“…), for example, dominance rank was not the best predictor of two measures of female reproductive success: offspring survival and longevity. Instead, females with the highest fitness were those with the strongest and most persistent bonds with other females [22][23][24][25]. Similar correlations between cooperative social bonds and components of fitness have been observed in a variety of other social mammals, including in particular humans [6].…”
Section: The Adaptive Value Of Social Bondsmentioning
confidence: 68%
“…), for example, dominance rank was not the best predictor of two measures of female reproductive success: offspring survival and longevity. Instead, females with the highest fitness were those with the strongest and most persistent bonds with other females [22][23][24][25]. Similar correlations between cooperative social bonds and components of fitness have been observed in a variety of other social mammals, including in particular humans [6].…”
Section: The Adaptive Value Of Social Bondsmentioning
confidence: 68%
“…As both humans and nonhuman primates are gregarious social animals who depend on their local conspecifics for aid in moderating life's stressors, research on allostatic load can contribute to socioecology as well as behavioral ecology theory. For example, olive baboons with high social connectedness had lower basal cortisol than those less socially connected (Ray & Sapolsky, 1992;Sapolsky, Alberts, & Altmann, 1997 connectedness have significantly reduced mortality risk (Archie, Tung, Clark, Altmann, & Alberts, 2014;Silk et al, 2010). Integrating allostasis theory and assessing ALIs across research on nonhuman primates alongside social and behavioral data also likely will aid research initiatives directed at improving health and management of captive populations, as well as informing conservation decision-making.…”
Section: Allostatic Load During Growth a N D De V E L O P Me N Tmentioning
confidence: 99%
“…Variation in survival is relatively straightforward to determine, provided individuals can be recognized and followed, but survival estimates are generally complicated by dispersal, and causes of mortality must be separated into those due to extrinsic causes (primarily predation) and those attributable to infection and non-infectious diseases. For example, Chapman et al [116] use demographic data collected over decades to make inferences about the effects of stress and new parasites on population dynamics in red colobus monkeys, and recent studies revealed that survival is affected by social relationships in female baboons [117] and male bottlenose dolphins [118].…”
Section: (D) Fitness Consequencesmentioning
confidence: 99%